The current trend of genomics research for human diseases - Zhang Ke K; Arabnia Hamid R; Wang Yunliang; Deng Youping (BMC, 2013)
Abstract This is an introduction to the supplement to BMC Medical Genomics that includes16 papers selected from the 2011 World Congress in Computer Science, Computer Engineering, Applied Computing as well as other sources with a focus on genomics studies with a focus on human diseases.